Evaluation of host effects on ectomycorrhizal fungal community compositions in a forested landscape in northern Japan. Issue 2 (19th February 2020) - Matsuoka, Shunsuke; Sugiyama, Yoriko; Tateno, Ryunosuke; Imamura, Shihomi; Kawaguchi, Eri; Osono, Takashi
Abstract : Community compositions of ectomycorrhizal (ECM) fungi are similar within the same host taxa. However, careful interpretation is required to determine whether the combination of ECM fungi and plants is explained by the host preference for ECM fungi, or by the influence of neighbouring heterospecific hosts. In the present study, we aimed to evaluate the effects of host species on the ECM community compositions in a forested landscape (approx. 10 km) where monodominant forest stands of six ECM host species belonging to three families were patchily distributed. A total of 180 ECM operational taxonomic units (OTUs) were detected with DNA metabarcoding. Quantitative multivariate analyses revealed that the ECM community compositions were primarily structured by host species and families, regardless of the soil environments and spatial arrangements of the sampling plots. In addition, 38 ECM OTUs were only detected from particular host tree species. Furthermore, the neighbouring plots harboured similar fungal compositions, although the host species were different. The relative effect of the spatial factors on the ECM compositions was weaker than that of host species. Our results suggest that the host preference for ECM fungi is the primary determinant of ECM fungal compositions in the forested landscape.